The advertising effect : how to change behavior - Ferrier, Adam, ....- (Victoria : Oxford University Press, 2018)
In The Advertising Effect, respected advertising insider, Adam Ferrier, reveals the ten techniques used by some of the best-known brands across the globe. These techniques are grounded in psychological theory with award winning real world examples and explore how the most effective way to change behaviour is through action rather than the conventional advertising practices (emotional or rational persuasion).
Keywords: Advertising; Reclame